Kaempferol and Quercetin Isolated from The Leaves of Atingia Excelsa to Arrest Cell Cycle in G0/G1 Phase Human Tongue Cancer SP-C1 Cell Lines - Risyandi Anwar; Arlette Setiawan; Supriatno; Unang Supratman (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2020)
The leaves of Altingia excelsa were found to strongly inhibit SP-C1 human tongue cancer cell lines. This study was focused on identifying the antiproliferative compound found in A. excelsa leaves and assessing its mechanism of action. The active compound was isolated using column chromatography and identified by the spectroscopic method and was also tested for its anti-proliferative properties and the cell cycle analysis in SP-C1 cells by flowcytometry analysis. This work resulted in the isolation of a flavonoid, which was identified to be kaempferol and quercetin. The compounds inhibited SP-C1 cell proliferation in a time- and dose-dependent manner with IC50 values of 0.72 µg/mL and 0. 70 µg/mL for the 24 hours treatments, respectively. Furthermore, the flowcytometry analysis suggested that the compounds exerted its anticancer activities by inhibiting cell cycle. These results suggested that compounds found in A. excelsa providies a basis for its potential use in cancer disease management.